Terek Region in Anthropological and Socio-Economic Dimensions of the First World War - Maria A. Ponomareva (RUDN Journal of Russian History)
Through their article, the author considers several aspects of the economic changes in the Terek region during the First World War: the role of the road transport network, the ratio of income and expenditure items of the budget, and the development of the main industries (horse breeding, agriculture, oil and processing industries). Attention is focused on new factors of the economic development of the Terek region, typical exclusively of the war period, in particular, the development of a medical institution to support the logging industry. The role of the Terek Cossacks, the Caucasian native cavalry division in the formation of an anthropological portrait of the North Caucasus is also considered. The author draws the conclusion about the impact of the First World War on the development of the Terek region, that it had anthropological and socio-economic dimensions. It is noted that the Terek region was an ideal model for overcoming the military crisis, not least because its inhabitants had, on the one hand, a collective identity, in which military service and military campaigns occupied an important place, and on the other hand, they also had a fragmented identity (the author singles out the collective identity of the Terek Cossacks and the collective and original identity of the mountain peoples).